A novel dissolution‐precipitation method for high‐efficiency separation of oil‐wetted oil sands. (10th December 2019) - Hu, Pengcheng; Chai, Ruimin; Liu, Quanyou; Wang, Junlin; Zhou, Shu‐Feng
Abstract: Dissolution‐precipitation is a novel high‐efficiency method for separating oil‐wetted oil sands. Four dissolving agents and three precipitating agents were studied to select the optimal combination. Results showed that N, N ‐dimethylcyclohexylamine (DMCHA) and methanol were the optimal dissolving and precipitating agents, respectively. The chemical group compositions, element content, and H/C atom ratio of bitumen separated by DMCHA‐methanol were analyzed, and the optimal conditions for oil sands separation were determined, under which the bitumen recovery reached 96.4%. After six separation cycles with DMCHA‐methanol, the bitumen recovery remained above 93%.